(3GdCZGfjs - (3Ydj Hf GdMSjf Hf eMeO Hf CMeO Hf GdgjKe GdeQhGfj GdCehj GdbQTj, CHh GdaQL GdCUHgGfj, J (B356 (3g` s ((3Ydj Hf HdOGf Hf SdWGf Hf eMeO s)
(3ChdgG (B:s
(3CJjfGc cjeG jYde GdfGS aVdfG EPG ELJeYhG hbJ EMJVGQ GdehGSe HCfG aQhY GdfGS aj cd ehWf hCf djS aj CQV GdMLGR cOGQe s
(3BNQgG (B:s
(3eG CQGfj Yf bQi GdQj eOi GdOgQ CQjje GdTYQ hGdZfGA dEHQGgje GdehUdj, hdLfg GdeNJGQ, Kbjd Chd fLR GdLRA GdQGHY s
(3GdNW eged GdfbW CMjGfkGs
(3ef fSNI KGefIs
(3hQO CjVkG JMJ Qbe (B2176s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs